(3LRA ef cJGH ajg JQGLe GdYjhfjjfs
(3ChdgG (B:s
(3hdbO CMSf GdbGFd ai GdYHGS hgh GdaVd Hf eMeO Hf GdaVd GHf GdMSf Hf YHOj Gddg Hf GdYHGS MjK jeOM LOg GdYHGS ai KHGJg eY CNjg GdMSjf Ydjg GdSdGe jhe GdWa s
(3BNQgG (B:s
(3JQcfG eWGa GdTYH hgj hLdg dce hefGN GdhGLHGJ LfhHgG heTYQ LeY hGdeaGV YTHg EPG MGd Ohf GdTeS bUQkG eYjHgG hef SGMQ hGdCHGWM cdgG hMjK EdJaJ CYdGe fhmH hdh HgG s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJGQjNs